Community Midwifery Practice PHBS Education In Households In Preventing Stunting In Toddlers - Irawati, Rita; Kustiani, Wahyu Nur Indah; Nurrofiqoh, Shinta Dwipa; Yantini, Yuli; Rahayu, Sulistio (Sean Institute, 2024)
Stunting is one of the chronic malnutrition problems in society, especially in toddlers. Stunting is caused by a lack of nutritional intake that occurs over a long period of time due to the provision of food that does not meet nutritional needs. The direct causes of stunting are inadequate nutritional intake and a history of infectious diseases, while indirect factors are parental knowledge about nutrition, parental education, parental income, and the number of family members. Stunting can be prevented by several things such as providing exclusive breastfeeding, consuming a variety of foods with a healthy and balanced menu, getting used to PHBS, doing physical activities such as exercising, giving supplements to toddlers and monitoring children's growth and development regularly or routinely taking them to the integrated health post. Empowerment and education to the community need to start from the household, especially for pregnant women and mothers with toddlers because children are assets or generations whose growth and development must be maintained. Based on the results of a pre-survey conducted from May 30-31, 2024 in Notoharjo Village with unstructured interviews conducted by researchers through interviews with 10 pregnant women and mothers of toddlers. From the interview results, it was stated that 8 people (80%) did not understand PHBS with stunting. While 2 people (20%) other mothers already understood PHBS with stunting. So the role of health workers plays an important role in providing education about the importance of PHBS with stunting which are interrelated. This aims to increase knowledge related to PHBS in reducing the incidence of stunting.